PERAMPASAN BARANG BUKTI UNTUK NEGARA TERHADAP TINDAK PIDANA NARKOTIKA (STUDI PUTUSAN NO: 342/PID.SUS/2022/PN.JKT.BRT): Confistering Evidence For The State On Narcotics Crime (Study of Decision No.342/pid.sus/2022/PN.JkTBrt) - Nabilla Andreas, Vanya Shafa; Saragih, Effendy (Faculty of Law, Universitas Trisakti, 2024)
Abstract Currently, drugs are misused to be consumed, distributed and marketed without obtaining permission from the authorities. The circulation of narcotics without permission or illegally is mostly carried out by irresponsible parties. Arrangements for a Confiscation and seizure for evidence in a narcotics criminal act have been regulated by the law, namely in Article 87 and Article 101 of Law Number 35 of 2009 concerning Narcotics. In the case of Decision Number 342/Pid.Sus/2022/PN.Jkt.Brt, the property of a third party used by the defendant was confiscated by the state which resulted in material losses for third parties. Based on the analysis from Decision Number 342/Pid.Sus/2022/PN.Jkt.Brt, the subject matter raised is 1) How is the consideration of the judge’s decision on decision Number: 342/Pid.Sus/2022/PN.Jkt.Brt if it is related to the Evidence Procedure contained in Law Number 35 of 2009 and The result of this research is the decision of a narcotics crime Number: 342/Pid.Sus/2022/PN.Jkt.Brt, who has confiscated evidence for the State in the form of third party property in accordance with the provisions contained in Article 101 paragraph (2) of Law Number 35 of 2009 concerning Narcotics.